Insights into the Effect of Heat Treatment and Carbon Coating on the Electrochemical Behaviors of SiO Anodes for Li‐Ion Batteries. Issue 18 (21st March 2022) - Xu, Shuai; Hou, Xiaodong; Wang, Dongniu; Zuin, Lucia; Zhou, Jigang; Hou, Yong; Mann, Michael
Abstract: The use of SiO as an anode material has attracted significant interest due to its high capacity and long cycling life. Many promising approaches, including structural design and carbon coating at high temperatures, effectively improve its intrinsic low electrical conductivity and poor Coulombic efficiency. However, the "heat treatment process‐composition and microstructure‐electrochemical properties" relationship of the SiO anode is not fundamentally understood. Here the structure and composition evolution in amorphous SiO and graphene‐coated SiO is investigated using different heat‐treatment conditions. X‐ray absorption near‐edge structure techniques are also employed to analyze the surface and bulk composition change during the initial lithiation process, supplemented by physical or chemical characterization and electrochemical testing. The results reveal the structural transition of SiO during heat treatment, from amorphous to disproportionated hierarchical structure, where the as‐formed dielectric exterior SiO2 shell and interior SiO2 matrix severely polarizes electrodes, hindering the lithiation process. Carbon coating on SiO effectively restricts the growth of the SiO2 shell and facilitates charge transfer, leading to improved electrochemical performance. A schematic model is proposed to reveal the relationship between the treatments, the resultant structural evolutions, and corresponding electrochemical behaviors. Abstract : SiO is among the top candidates for next‐generation lithium‐ion battery anodes. Heat treatment and carbon coating are two widely used approaches that make SiO anodes succeed. The fundamental "process‐microstructure‐electrochemical performance" relationship is thoroughly investigated and understood. The findings offer crucial insights for the future design and application of SiO‐based anode materials.